Cognitive Impairments Preceding and Outlasting Autoimmune Limbic Encephalitis - Robert Gross; Jennifer Davis; Julie Roth; Henry Querfurth (Case Reports in Neurological Medicine)
Mild cognitive impairment (MCI) can be the initial manifestation of autoimmune limbic encephalitis (ALE), a disorder that at times presents a diagnostic challenge. In addition to memory impairment, clinical features that might suggest this disorder include personality changes, agitation, insomnia, alterations of consciousness, and seizures. Once recognized, ALE typically responds to treatment with immune therapies, but long-term cognitive deficits may remain. We report two cases of patients with MCI who were ultimately diagnosed with ALE with antibodies against the voltage gated potassium channel complex. Months after apparent resolution of their encephalitides, both underwent neuropsychological testing, which demonstrated persistent cognitive deficits, primarily in the domains of memory and executive function, for cases 1 and 2, respectively. A brief review of the literature is included.